A Friendly Environment Approach for determination of paracetamol - Hanaa Mahmood (College of Education for Pure Sciences, 2020)
Abstract This paper involves a determination of paracetamol using less environment harmful reagent; the hydroxy analog of the pharmaceutical naproxen replaced a chemical reagent in which it is used as a coupling agent for the diazotized p-aminophenol (the hydrolysis product of paracetamol), the paper offers a determination of an analgesic paracetamol in the presence of high content of another analgesic. Paracetamol azo-dye exhibits maximum absorption at 500 nm. Beer's law is obeyed over the concentration range from 10 to 650 µg/20ml, (i.e. 0.5-32.5 ppm) with a good sensitivity (molar absorptivity 1.2x104 l.mol-1.cm-1), good precision (RSD better than ±0.275%) and high accuracy (relative error less than + 0.77%), Sandell's sensitivity index is 0.0124µg.cm-2, the limit of detection (LOD) is 0.0030 µg/ml and the limit of quantitation (LOQ) is 0.0101 µg/ml. The method has been successfully applied for determination for paracetamol in dosage forms and its already applicable for the determination of paracetamol in presence of naproxen.